Grief and ruminative thought after perinatal loss among Turkish women: one-year cohort study - Gozuyesil, Ebru; Manav, Ayse Inel; Yesilot, Saliha Bozdogan; Sucu, Mete (São Paulo Medical Journal, 2022)
BACKGROUND: Among women who have suffered loss of pregnancy, the level of grief decreases gradually. Age, mental health status and childlessness are the factors known to mostly affect women’s levels of grief. OBJECTIVES: To assess the levels of grief among women who experienced perinatal loss and the changes in their ruminative thought styles over the first year after their loss. DESIGN AND SETTING: One-year follow-up study carried out in a university hospital in Turkey. METHODS: The study population included 70 women who experienced loss of pregnancy in the hospital. The sample size was calculated using G*Power V3.1. Data were collected at 48 hours, at the third month, at the sixth month and at one year after pregnancy loss, between June 2018 and June 2019. A personal information form, the Perinatal Grief Scale and the Ruminative Thought Style Questionnaire were used for data collection. RESULTS: The women’s highest levels of grief and ruminative thought style were in the first 48 hours. Their tendency towards grief and ruminative thought styles decreased over the repeated measurements during the follow-up. Women aged 20-29 years had the highest levels of grief at the third month after perinatal loss. CONCLUSIONS: Nursing assessments regarding grief and ruminative thought style over the first 48 hours after perinatal loss should be integrated into nursing care for these women. Grief follow-up programs for these women can be developed through nursing research.